Effect of wood flour as nucleating agent on the isothermal crystallization of poly(lactic acid). (27th July 2016) - Wu, Wendi; Wu, Guangfeng; Zhang, Huixuan
Abstract : The effect of wood flour (WF) as an efficient nucleating agent on the isothermal melt crystallization and isothermal cold crystallization behavior of poly(lactic acid) (PLA) was investigated by differential scanning calorimeter and polarized optical microscopy. It was found that the incorporation of 4 wt% WF promoted the crystallization of PLA about 4.2%. Polarized optical microscopy results showed the Maltese cross of the samples. The presence of the 4 wt% WF may increase the nucleation density, leading to the increase of the spherulites; however, the size of the spherulites decreased, and the structure became incomplete. The Avrami model was applied to analyze the isothermal crystallization kinetics. It is concluded that the addition of WF modified the crystallization process of PLA (the value of Avrami exponent changed). Various parameters, such as the crystallization half time and crystallization rate constant, reflect that 4 wt% WF significantly improves the crystallization process. The observations in this article indicate that WF is an efficient nucleating agent of PLA. Copyright © 2016 John Wiley & Sons, Ltd.